1988
DOI: 10.1002/1097-0142(19880115)61:2<379::aid-cncr2820610230>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Nonpharmacologic factors in the development of posttreatment nausea with adjuvant chemotherapy for breast cancer

Abstract: A prospective, longitudinal design was used to determine the role of nonpharmacologic factors in the development of posttreatment nausea (PTN). Forty-five women with no previous chemotherapy experience who were receiving a single regimen of adjuvant chemotherapy for breast cancer were interviewed before and after their first six infusions. Seventy-one percent of patients developed PTN. The PTN was related to the following: patients' physical status at the onset of treatment; heightened anxiety during infusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
2
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 17 publications
7
75
2
1
Order By: Relevance
“…While the relationship between state anxiety and gastrointestinal distress has been discussed earlier (23)(24)(25), little research has examined the relationship between state anxiety and PNV. An exception is the study by Jacobsen et al (51). Using a multivariate model, they found that state anxiety was associated with a greater prevalence, frequency, and severity of postchemotherapy nausea.…”
Section: Causal Relationships Between Anv and Anxietymentioning
confidence: 98%
“…While the relationship between state anxiety and gastrointestinal distress has been discussed earlier (23)(24)(25), little research has examined the relationship between state anxiety and PNV. An exception is the study by Jacobsen et al (51). Using a multivariate model, they found that state anxiety was associated with a greater prevalence, frequency, and severity of postchemotherapy nausea.…”
Section: Causal Relationships Between Anv and Anxietymentioning
confidence: 98%
“…7,[24][25][26] Anxiety is known to affect the development of NV at least in part through negative expectancies, 24,[27][28][29] and, reciprocally, negative expectancies are instrumental in the development of anxiety. 16,30 Expectancies affect the generation of conditioning effects, [31][32][33] and, conversely, conditioning influences response expectancies.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that the relationship between anxiety and nausea is based primarily on the higher probability of occurrence of nausea in subjects with higher anxiety levels [2,21,23,37,42], and correlations between degree of anxiety and magnitude of nausea are weak [27,44]; the present A C C E P T E D M A N U S C R I P T study only models the latter situation. Taking the results at face value, motion clearly produced hypothermia in all three lines, and this is consistent with previous studies of hypothermia induced by a number of emetic stimuli in both rats (lacking an emetic reflex [19]) and Suncus murinus (with an emetic reflex) [9,17,35].…”
Section: Do Our Findings Challenge the Validity Of The "Hypothermia Nmentioning
confidence: 75%
“…Nausea and vomiting are among the key symptoms of generalized anxiety disorder and of panic attacks [31]. Anxious subjects are more susceptible to anticipatory and therapeutic-induced nausea and vomiting resulting from chemotherapy [2,21], and the level of nausea and vomiting following surgery is positively correlated with preoperative anxiety magnitude [28,44]. Anxiety is considered to be a sensitising factor for air and motion sickness [23,37,42], and subjects with a better ability to handle stress have a lower risk of being motion sick [20].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%